Pengaruh Balance Exercise Terhadap Keseimbangan Dinamis Pasca Cidera Sprain Ankle Pada Pemain Futsal Big Family Fc Di Serdang Bedagai - Putri Lutfia Hakim; Wahyu Wijanarko; Yeni Vera (Jurnal Kesehatan dan Fisioterapi, 2022)
Ankle sprains are injuries that occur due to overstretching and hypermobility or trauma to the lateral complex ligaments, by sudden inversion and plantar flexion forces during exercise, physical activity, when the foot is not fully supported on the floor or ground, causing ligaments are stretched beyond their normal physiological and functional length. Stretching causes tears in the lateral complex ligaments, this will cause pain when contracted. The pain causes immobilization resulting in a decrease in muscle strength and limitation of motion (Calatayud, 2014). Balance Exercise is designed to increase the neuromuscular efficiency of the entire body movement system. This exercise involves dynamic eccentric and cocentric movements of the foot balance. The movements performed require dynamic control in the middle of the range of motion, with isometric stabilization at the end of the movement (Clark, 2014). The purpose of this study was to determine the effect of balance exercise on the dynamic balance of athletes after ankle sprains in BFC (Futsal Big Family FC) players with 20 male athletes with ankle sprains grades 2 and 1, aged 15-19 years. This research method uses one group only pre test - post test with purposive sampling technique. Results Based on the test, it is found that the hypothesis test above is known to be 0.000 where the lift is smaller than so it can be concluded that there is an influence between pre and post exercise on improving balance. Conclusion Thus, it is hoped that futsal players who suffer from ankle sprains can improve dynamic balance with balance exercises. Keywords: Balance Exercise, Dynamic Balance, Sprain Ankle